Political trends in Al-Jahid's literature - الجميلي, محمد كريم (Al-Adab Journal, 2019)
Al-Jahid Known as a writer impose himself in his own time and in subsequent ages, In addition, he was a political veteran who has lived his life defending his opinions and ideas. Al-Jahid was a senior expressive for the nation's unity and consistency of its elements and races and preserve Arabic authenticity, Because the idea of the nation's unity was one of the core messages of Islam, and is the base of succession in governance philosophy. So his books came in the virtues of clans, tribes, cities that are looking for combining what does not differentiate in order to establish a balance between people of different races.